The predictive value of an adjusted COPD assessment test score on the risk of respiratory-related hospitalizations in severe COPD patients. (February 2017) - Sloots, Joanne M; Barton, Christopher A; Buckman, Julie; Bassett, Katherine L; Palen, Job van der; Frith, Peter A; Effing, Tanja W
We evaluated whether a chronic obstructive pulmonary disease (COPD) assessment test (CAT) with adjusted weights for the CAT items could better predict future respiratory-related hospitalizations than the original CAT. Two focus groups (respiratory nurses and physicians) generated two adjusted CAT algorithms. Two multivariate logistic regression models for infrequent (≤1/year) versus frequent (>1/year) future respiratory-related hospitalizations were defined: one with the adjusted CAT score that correlated best with future hospitalizations and one with the original CAT score. Patient characteristics related to future hospitalizations ( p ≤ 0.2) were also entered. Eighty-two COPD patients were included. The CAT algorithm derived from the nurse focus group was a borderline significant predictor of hospitalization risk (odds ratio (OR): 1.07; 95% confidence interval (CI): 1.00–1.14; p = 0.050) in a model that also included hospitalization frequency in the previous year (OR: 3.98; 95% CI: 1.30–12.16; p = 0.016) and anticholinergic risk score (OR: 3.08; 95% CI: 0.87–10.89; p = 0.081). Presence of ischemic heart disease and/or heart failure appeared 'protective' (OR: 0.17; 95% CI: 0.05–0.62; p = 0.007). The original CAT score was not significantly associated with hospitalization risk. In conclusion, as a predictor of respiratory-related hospitalizations, an adjusted CAT score was marginally significant (although the original CAT score was not). 'Previous respiratory-related hospitalizations' was the strongest factor in this equation.